Distribution of water in the pores of periodic mesoporous organosilicates - a proton solid state MAS NMR study - Veena, V. S.; Illath, Kavya; Lazar, Anish; Vinod, C. P.; Ajithkumar, T. G.; Jayanthi, S. (Physical Chemistry Chemical Physics, 2018)
Solid state proton (H-1) magic angle spinning (MAS) NMR has been employed to study the distribution of confined water in ethane substituted periodic mesoporous organosilicate (PMOE) materials. Proton spectra acquired at different hydration levels are analysed and interpreted in terms of water clusters of various sizes and distributions of water layers on the pore surface. For comparison, we also performed similar experiments on SBA-15. The formation of larger clusters at lower hydration suggests that the pores of PMOE are getting filled with water at lower hydration levels than those in SBA-15. For PMOE, the simultaneous presence of two major resonances in the ranges 3.6-4.1 ppm and 4.4-5.2 ppm and their behaviour upon hydration imply a water layer distribution that is the sum of two contributions, corresponding to fully filled and partially filled pores or pore segments. Furthermore, the behaviour mentioned above suggests that both radial and axial filling mechanisms play a significant role in the hydration process. For SBA-15, as a function of hydration, we observed a smooth variation in the proton chemical shift of the main dynamic resonance. In accordance with previous studies, this is attributed to the gradual increase in the average thickness of water layers with an increase in hydration, and to a pore filling mechanism that is predominantly radial.